Banana Hump Starch and Ginger Extract as Edible Coating to Extend the Shelf-life of Red Chili Peppers - Restuhadi, Fajar; Ayu, Dewi Fortuna; Nuratika, Nuratika (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2023)
AbstractFresh red chili peppers is a product that spoils easily and has a concise shelf-life. Coating a natural edible coating on fresh red chili peppers will significantly increase their shelf-life. This research aims to obtain the best concentration of ginger extract in the edible coating of banana hump starch to extend the shelf-life of red chili peppers. The research was carried out experimentally using a completely randomized design with five treatments and three replications. The treatment in this research was an edible coating of banana hump starch with the addition of various concentrations of ginger extract; J0 (0%), J1 (1%), J2 (3%), J3 (5%), and J4 (7%); which were applied on red chili peppers for 15 days of storage. The parameters observed were weight loss, vitamin C, total microbes, and sensory assessment. The best treatment in this study was J4 (addition of 7% ginger extract). On the 15th day of storage, red chili peppers coated with edible coating treated with J4 experienced a reduction in weight loss of 41.20%, with 18.54 mg/100g of vitamin C and 5.89 log CFU/g of total microbes. Descriptive tests showed that on the 15th day of storage, red chili peppers had a red color, started to smell and taste rotten, and had a slightly hard texture.Keywords: edible coating, ginger extract, red chili peppers Abstrak         Cabai merah segar merupakan produk yang sangat mudah membusuk dan memiliki umur simpan yang sangat pendek. Pelapisan edible coating alami pada cabai merah segar akan sangat efektif dalam upaya meningkatkan umur simpan dari cabai merah. Penelitian ini bertujuan untuk mendapatkan konsentrasi terbaik ekstrak jahe dalam edible coating pati bonggol pisang untuk memperpanjang masa simpan cabai merah. Penelitian dilaksanakan secara eksperimen menggunakan rancangan acak lengkap dengan lima perlakuan dan tiga ulangan. Perlakuan dalam penelitian ini adalah edible coating pati bonggol pisang dengan penambahan berbagai konsentrasi ekstrak jahe, yaitu J0 (0%), J1 (1%), J2 (3%), J3 (5%), dan J4 (7%) yang diaplikasikan pada cabai merah selama 15 hari penyimpanan. Parameter yang diamati adalah susut bobot, vitamin C, total mikroba, dan penilaian sensori. Perlakuan terbaik pada penelitian ini adalah J4 (penambahan ekstrak jahe 7%). Pada penyimpanan hari ke-15, cabai merah yang dilapisi edible coating perlakuan J4 mengalami penurunan susut bobot 41,20%, dengan 18,54 mg/100g vitamin C dan 5,89 log CFU/g total mikroba. Uji deskriptif menunjukkan bahwa pada penyimpanan hari ke-15, cabai merah memiliki warna merah, mulai berbau dan berasa busuk, serta tekstur agak keras.Kata Kunci: edible coating, ekstrak jahe, cabai merah